Autonomous farming and monitoring system of vegetables in sustainable rooftop environment - Mafuj, Walid Ahmad; Rahman, Meer Tahmidur; Biswas, Shantanu; Islam, Tamanna (2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.